The genetic legacy of a global marine invader - Erik E. Sotka; Ryan B. Carnegie; James T. Carlton; Lucia Couceiro; Jeffrey A. Crooks; Hikaru Endo; Hilary Hayford; Masakazu Hori; Mitsunobu Kamiya; Gen Kanaya; Judith Kochmann; Kun-Seop Lee; et al. (Proceedings of the National Academy of Sciences, 2025)
The massive geographic expansion of terrestrial plant crops, livestock, and marine aquacultured species during the 19th and 20th centuries provided local economic benefits, stabilized food demands, and altered local ecosystems. The invasion history of these translocations remains uncertain for most species, limiting our understanding of their future adaptive potential and historical roles as vectors for coinvaded species. We provide a framework for filling this gap in invasion biology using the widely transplanted Pacific oyster as a case study. A two-dimensional summary of population-level variation in single nucleotide polymorphisms in native Japan reflected the geographical map of Japan and allowed identification of the source regions for the worldwide expansion. Pacific oysters proliferate in nonnative areas with environmental temperatures similar to those areas where native lineages evolved. Using Approximate Bayesian Computation, we ranked the likelihood of historical oyster or shipping vectors to explain current-day distribution of genotypes in 14 coinvaded algal and animal species. Oyster transplants were a more likely vector than shipping for six species, shipping activity was more likely for five species, and a vector was ambiguous for three species. Applying this approach to other translocated species should reveal similar legacy effects, especially for economically important foundation species that also served as vectors for nonnative species.